THE BURDEN OF PROOF IN THE ADMINISTRATIVE PROCESS IN ALBANIA - Hoxhaj, Entela; Baraku, Irma (European Scientific Journal, ESJ, 2014)
The role of the administrative authority is different in theadministrative process in the administrative proceedings and inadministrative adjudication. This difference is seen in its possibility toimpose rules to the private parties in the administrative proceeding and in itsbeing equall part in the administrative conflict in court.With the enactment of the law on administrative courts in albania there arenew rules of admnistrative judging. These rules are related also with theburden of proof which is different from the classic rule for the burden ofproof in the civil processes in court. This is the main object of treatment ofthe following paper. The burden of proof in the adminsitrative adjudicationbelong to the public authority and this is one of the main principles ofadministrative judging.